Immunoglobulin heavy chain expression shapes the B cell receptor repertoire in human B cell development - Meffre, Eric; Milili, Michèle; Blanco-Betancourt, Carla; Antunes, Henedina; Nussenzweig, Michel C.; Schiff, Claudine (The Journal of Clinical Investigation, 2001)
Developing B cells must pass a series of checkpoints that are regulated by membrane-bound Igμ through the Igα-Igβ signal transducers. To determine how Igμ expression affects B cell development and Ab selection in humans we analyzed Ig gene rearrangements in pro-B cells from two patients who are unable to produce Igμ proteins. We find that Igμ expression does not affect VH, D, or JH segment usage and is not required for human Igκ and Igλ recombination or expression. However, the heavy and light chains found in pro-B cells differed from those in peripheral B cells in that they showed unusually long CDR3s. In addition, the Igκ repertoire in Igμ-deficient pro-B cells was skewed to downstream Jκs and upstream Vκs, consistent with persistent secondary V(D)J rearrangements. Thus, Igμ expression is not required for secondary V(D)J recombination in pro-B cells. However, B cell receptor expression shapes the Ab repertoire in humans and is essential for selection against Ab’s with long CDR3s.